2017
DOI: 10.1063/1.5016737
|View full text |Cite
|
Sign up to set email alerts
|

Welding of bio-based plastics for applications in the field of injection moulding

Abstract: Abstract. Due to intensive research in the field of material development considerable progress in terms of processing and performance characteristics could be achieved during the last years. Therefore, bio-based plastics are increasingly being used for the production of durable injection moulded components. Several applications can be found in the automotive sector, in the field of consumer electronics or the sports industry. For an economic production, joining technology often plays a key role to realise modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This work showed that moldings in a range of 100 nm to 300 µm with an aspect ratio from 1 to 10 were possible by laser molding and this new process was flexible in using different mold inserts and molding materials and sizes. Hopmann and Schongart employed an external high power diode laser scanner to the heat mold surface. The laser parameters, heating time, area‐related energy density and the spot diameter, influenced the temperature profile during the heating period.…”
Section: Various Heating Methods For Variotherm Processmentioning
confidence: 99%
“…This work showed that moldings in a range of 100 nm to 300 µm with an aspect ratio from 1 to 10 were possible by laser molding and this new process was flexible in using different mold inserts and molding materials and sizes. Hopmann and Schongart employed an external high power diode laser scanner to the heat mold surface. The laser parameters, heating time, area‐related energy density and the spot diameter, influenced the temperature profile during the heating period.…”
Section: Various Heating Methods For Variotherm Processmentioning
confidence: 99%